Barriers to methamphetamine treatment seeking in residential centers in Aguascalientes, Mexico - Martínez Martínez, Kalina Isela; Ojeda Aguilar, Yancarlo Lizandro; Robles Villarreal, Lorenia; Paz Pérez, María Abigail (Frontiers in Psychology, 2023)
Introduction In the Aguascalientes, most people who seek treatment go to non-governmental residential centers, and about half request treatment for meth use. Although some barriers to treatment seeking among these users are known, few studies have been conducted with the Mexican population, specifically with users of residential centers. The aim of this study was to explore the main barriers reported by these patients, the relationship between reported barriers and meth use, as well as identify possible user profiles based on the barriers and the pattern of consumption. Methods We designed a brief survey that evaluated sociodemographic data, consumption pattern, help-seeking for consumption and use of services, barriers in the search for services, depression, and suicide attempts. Here, we report the results of barriers and consumption patterns. The study sample consisted of 865 individuals receiving treatment for meth use in 23 certified residential centers. Results Patients reported an average of 2.12 barriers, the main ones being not considering the services useful for them (41.6%), not considering it important to attend (35%), and not finding time to attend the consultation (29.8%). We found a statistically significant relationship, although weak, between the number of barriers reported by participants and the age of onset of meth use, dangerous perception of meth use, attempts to quit, and the number of problems associated with use. We used a cluster analysis that was performed using the k-means machine learning algorithm, which revealed two clusters. The first was formed by patients who started using meth at a young age which has more problems associated with meth use and more barriers in seeking services, while the other was formed by patients who started at an older age which have fewer problems and fewer barriers. We found statistical differences between groups, where it was found that young group reported consuming more substances, more problems associated, and more barriers in seeking services. Discussions This study revealed the main barriers to seeking treatment among patients in residential centers and found that the age of onset of meth use is a risk factor for presenting more barriers and more problems associated with consumption.